Safe Surgical Pathology Material Management in the Operating Room - Semra Bülbüloğlu; Kadir Sevin; Sadık Çakır; Fatma Eti Aslan (Association of Nurse Managers, 2017)
Background: Surgical pathology material management (SPMM) is creating a important part of patient safety in operating room. Removed from patients surgical pathology materials (SPM) play a key role for diagnosis and correct treatment. When SPMM made effectively, a new intervention can need to be as psychological and physical for patient. While SPMM realized no take protector security precautions, health care workers possible to exposure blood, body fluids, chemical hazards and other potentially infection materials. Despite known importance of SPMM, it isn't a level of ideal alpications about SPMM in Turkey and in the world. Aim: The aim of this study; prepared a review for guideline about how of SSPM. Material and Methods: A review that contain of recommendations for effectiveness SSPM prepared by Association of perioperative Registered Nurses-AORN, books, articlesand studies was reviewed and prepared a guideline about how of SPMM. In context of this guideline taken criteria designate as 1) It was published a scientific journal national/international with referee. 2) In context of scientifically evidences about how of SSPM process 3)It was correlated perioperative nursing with SPMM. Findings: The result of literature search was appointed a little od study about how of SPMM, in recent years it was determined that a concept frequently highlihted and being developed. Whenever it was done not effective, more problems reveals for patient and personnel. Coclusion: In context of this study is located recommendations for interventions available patient safety in operating room. While the institutional policy, procedures, protochol was prepared, institutions can implement a level of optimal patient safety standards. Records should be to keep correct and no deficient on the perioperative process. Patient and personnel security should be protected every stage of SPMM.